Pengaruh Penggunaan Youtube untuk Kemampuan Berbicara pada Anak Usia 4-5 Tahun - Nailul Fadhillah; Kusumawardani, Ratih; Rosidah, Laily (Generasi Emas, 2023)
Speaking is one of language skills that exist in early childhood, speaking is an activity to clearly express an idea, the purpose or feeling so another individual could understand what is meant and can be stimulated for early childhood in everyday activites. Speak ability is a skills that can be carried out by an individual to be able finished a job properly and this ability is acquired since birth and can be honed further through stimulation from family or people around children so can develops and produces with maximum results. YouTube is application that we used through accessed an Internet, the user could send or display videos and animations with various video so people can enjoy it. The research was conducted in Uwung Jaya Village, Tangerang, Banten. The research used a quantitative method, Expost factor, and purposive sampling where the subjects were parents who had 4- to 5-year-old children that watched YouTube. The samples taken were 30 parents. The data collection technique used questionnaires, and the data analysis used normality test, linearity test, simple linear regression test, and t-test. The analysis shows a data yield of 0,657 with a significance value of 0,000 < 0,05, which means H0 is rejected and H1 is accepted; therefore, the result indicates there is an influence by YouTube for children's speaking abilities aged 4 to 5 years old by 43,2 % or 0,432.